Macrophage‐tropic HIV‐1 variants from brain demonstrate alterations in the way gp120 engages both CD4 and CCR5. Issue 1 (1st January 2013) - Salimi, Hamid; Roche, Michael; Webb, Nicholas; Gray, Lachlan R.; Chikere, Kelechi; Sterjovski, Jasminka; Ellett, Anne; Wesselingh, Steve L.; Ramsland, Paul A.; Lee, Benhur; Churchill, Melissa J.; Gorry, Paul R.
Abstract : Along with an enhanced interaction with CD4, highly M‐tropic HIV‐1 Envs have an altered mechanism of engagement with CCR5. Abstract : BR‐derived HIV‐1 strains have an exceptional ability to enter macrophages via mechanisms involving their gp120 Env that remain incompletely understood. Here, we used cell‐based affinity‐profiling methods and mathematical modeling to generate quantitative VERSA metrics that simultaneously measure Env‐CD4 and Env‐CCR5 interactions. These metrics were analyzed to distinguish the phenotypes of M‐tropic and non‐M‐tropic CCR5‐using HIV‐1 variants derived from autopsy BRs and LNs, respectively. We show that highly M‐tropic Env variants derived from brain can be defined by two distinct and simultaneously occurring phenotypes. First, BR‐derived Envs demonstrated an enhanced ability to interact with CD4 compared with LN‐derived Envs, permitting entry into cells expressing scant levels of CD4. Second, BR‐derived Envs displayed an altered mechanism of engagement between CD4‐bound gp120 and CCR5 occurring in tandem. With the use of epitope mapping, mutagenesis, and structural studies, we show that this altered mechanism is characterized by increased exposure of CD4‐induced epitopes in gp120 and by a more critical interaction between BR‐derived Envs and the CCR5 N‐terminus, which was associated with the predicted presence of additional atomic contacts formed at the gp120‐CCR5 N‐terminus interface. Our results suggest that BR‐derived HIV‐1 variants with highly efficient macrophage entry adopt conformations in gp120 that simultaneously alter the way in which the Env interacts with CD4 and CCR5.